INVESTIGATING THE IMPACT OF ONLINE VS. BLENDED LEARNING ON VOCABULARY LEARNING: EVIDENCE FROM IRANIAN INTERMEDIATE EFL LEARNERS - Ramezani Sarajari, Maryam; Pourhosein Gilakjani, Abbas (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This study aimed to examine the effect of online vs. blended learning on improving vocabulary learning among Iranian intermediate EFL learners. The current study followed a quasi-experimental, pretest-posttest control group research design. The researchers selected a sample of 120 EFL intermediate learners from a private English Language Institute in Lahijan, Iran for this purpose. The researchers divided the participants into three groups of 40 students each. The researchers used three instruments: 1) a Solution Placement Test (SPT), 2) a Vocabulary pre-test 3), and Vocabulary post-test. The control group only learned vocabulary through traditional lecture methods and face-to-face teaching. The LMS instructional model and the blended learning instructional model were used to teach vocabulary to the online learning group and the blended learning group, respectively. After 10 weeks, students were tested again using a before and after design. In the L2 vocabulary test, both the online and blended learning groups performed better than the control group, in addition, no significant difference was observed between the online and blended learning groups. That is, both online and blended learning instructions have been effective in the development of EFL learners’ vocabulary learning and have had a statistically significant effect on the vocabulary learning of Iranian intermediate EFL learners. The researchers suggest that EFL students can benefit from learning L2 vocabulary through online and blended learning. The findings have practical implications for teacher education programs to promote prospective teachers’ interest and willingness to implement web-based systems. The findings also have important implications for web-based application developers. They should consider a clear model for blended learning and teachers should have the right to choose a blended learning model that suits their teaching contexts to manage the classroom and provide a more effective learning environment.